Economic Growth and the Environment: Whose Growth? Whose Environment? - Beckerman, W (1992)
The widespread clamor for immediate draconian action to reduce the danger of global warming is an unjustifiable diversion of attention from the far more serious environmental problems facing developing countries. Resource constraints do not constitute limits to growth, and the likely economic damage done by climate change would be a negligible proportion of world output. The loss of welfare of the population in developing countries today as a result of inadequate access to safe drinking water and sanitation, or of urban air pollution, is far greater and should be given priority over the interests of future generations. The "sustainable" growth concept is either morally indefensible or totally nonoperational.